Parasitoid of coffee berry borer, Hypothenemus hampei Ferrari (Coleoptera: Curculionidae) at Bogor District, West Java, Indonesia - HIKSA MAULANA SAPUTRA; NINA MARYANA; PUDJIANTO PUDJIANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Saputra HM, Maryana N, Pudjianto. 2023. Parasitoid of coffee berry borer, Hypothenemus hampei Ferrari (Coleoptera: Curculionidae) at Bogor District, West Java, Indonesia. Biodiversitas 24: 6447-6453. The coffee berry borer (CBB), Hypothenemus hampei Ferrari (Coleoptera: Curculionidae), is an essential pest of coffee plants that can cause loss and decrease in the quality of coffee berries. Parasitoids were expected to affect the presence of coffee berry borer in the ecosystem as one of its natural enemies. This study aimed to identify and describe the parasitoid of CBB in Bogor District, West Java, Indonesia. The study was conducted from June 2022 to January 2023 on three coffee cultivation located in three sub-districts in Bogor District, i.e., Cijeruk, Dramaga, and Sukamakmur. This study collected attacked coffee berries by CBB from coffee cultivation that kept the coffee berry until the parasitoids emerged and the parasitoids were identified; the morphological characters and descriptions of parasitoids CBB were presented. Ten species of Hymenopteran parasitoids belonging to five families were found. These parasitoids were Microgastrinae, Mendesellinae (Braconidae), Trissolcus sp. (Scelionidae), Anagyrus sp., Marxella sp., Procheiloneurus sp., Pararhopella sp., Parablastothrix sp. (Encyrtidae), Pronotalia sp. (Eulophidae), and Pteromalus sp. (Pteromalidae). The parasitoids of CBB in Bogor District were quite diverse, but their abundance was low.